The ecosystem of newsstands: a study about a species in extinction - Silva, Luciano Ferreira da; Fiqueiredo, Jocely Santos; Santos, Bruno Quintiliano dos (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
This study aimed to analyze changes in market newsstands through the concepts of the Theory of Organizational Ecology of Populations (FREEMAN; HANNAN, 2005; CUNHA, 1999; BAUM, 1999; SWAMINATHAN, 1996). Therefore, this study was conducted using the deductive method of exploratory mode, being conducted by qualitative approach through content analysis on data collected from secondary sources and interviews. Based on these analyzes could be perceived that managers of organizations surveyed try to adapt these for survival. However, as much as the owners of the newsagents and other stakeholders as the public sector try to impose a rationality that incorporates other products and change the way of arranging them, as these species undergo a process of extinction. Thus, with the change in this population is necessary organizational another managerial, legal and marketing treatment because they must be taken into account factors related to the rationality of the environment.